ENGLISH CODE MIXING USED IN THE MAGIC HOUR NOVEL - Chandra Ivan (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
The objectives of this study are (1). To find the types of code mixing used in the novel Magic Hour. (2). To know the Indonesian meaning of code mixing used in the novel Magic Hour. (3). To know the most typical type code mixing used in the novel Magic Hour. This research uses descriptive qualitative method to collect the data. The data are the English words. The writer collects data by finding the types of Indonesian English code mixing, selecting sentence that consist of Indonesian-English code mixing. The analysis shows that there are some types that use, such as: Intra sentential mixing, intra lexical code mixing, involving a change of pronunciation. The types of code mixing which found in the novel are selected into the most typical forms. The writer looked for Indonesian meaning of code mixing. The achievements of this research are expected to be additional source of code mixing study and it is meant to conduct and to develop in the code mixing field.